Emosional dan Penyakit Kejiwaan dalam Al-Qur`an - Farid, Ahmad; Chanifa, Siti Dian Millati; Mardiyah, Reva; Murodli, Najwa Nida; Milatunnajiyah, Milatunnajiyah; Sya`adah, Khaeru Mela; Sadiah, Sadiah (Lembaga Intelektual Muda (LIM) Maluku, 2023)
In the Qur'an, meticulous descriptions of the various emotions felt by human beings, such as fear, anger, love, joy, hatred, and sadness are expressed. Psychiatric illness is a personality disorder characterized by mental emotional disturbances. This study aims to find out the Quranic views on emotions and various mental illnesses, as well as how to overcome them. This research uses a qualitative approach through literature studies. Data collection is carried out through analysis of various sources including books, scientific articles, and relevant documents. Data analysis uses qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. The results of the data analysis show that the Qur'an provides instructions on how to manage emotions. The Quran gives instructions on how to manage emotions properly and correctly to give birth to emotional intelligence. Then to develop emotions and mental illnesses to have a positive impact, it is necessary to make efforts to understand the Qur'an, to allow them to channel various desires that cannot be realized in real life or neutralize various emotions and negative mental illnesses that exist in them.